PERFORMANCES COMPARISON BETWEEN URBAN AND RURAL PIG FARMING SYSTEMS IN MANOKWARI, WEST PAPUA PROVINCE INDONESIA - Desni Triana Ruli Saragih; Deny Anjelus Lyai (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
Pigs are kept both in urban and rural areas. This research identified the performance differences between urban and rural farming systems. The study was conducted in Manokwari regency and involved six districts, i.e. Nothern Manokwari district, Eastern Manokari District, Western Manokwari district,Warmare district, Prafi district and Masni district. Data were analyzed using SPSS version 18.0, an independent-samples T test was run to compare urban and rural pig farming systems. The research found that there were differences of ages and feeding hours (P<0.05) between those two farming systems. Therewere no differences in household members, experience, average pig owned, working hours, selling period, litter size and number of farrowing. There are nine point of pig farming improvement that should be done to sustain pig farming systems in Manokwari Papua. Education may be improved by provide informal and skillful education. Pig ownership should be increased. Working hours must be increased. Pig keeping in the pens should be done by farmers. Managing pigs with additional time is important so that pigs will be maintained well. Litter sizes both in urban and rural are low, therefore further improvements are needed. Recording pig productivities must be done by every farmer.(Key words: Arfak pig farmers, Pig performance, Rural pig farming, Urban pig farming)